ANALYSING LEARNING STYLES USED BY THE SEVENTH-GRADE STUDENTS AT MTsN 2 BULUKUMBA IN LEARNING ENGLISH - Andi Kaharuddin; Nurul Fitra; Multazam Abubakar (International Conference on Social and Islamic Studies, 2021)
This research focuses on the students’ learning style in learning English. The purposes of this research is to find out the students’ learning style preferences in learning English. The researcher uses qualitative method. The population of this research is the seventh-grade students at MTsN 2 Bulukumba. The sample of this research are 50 students from two classess. The researcher uses questionnaire and interview to collect the data and microsoft excel to analyse the data. The findings shows that students preferred authority-oeriented style the most and analytical style as the least preferred when they were studying English. Students approach in learning English most likely afected by teacher’s influence. Moreover, students did not have a strong preference towards individual learning in studying English. In conclusion, among the four learning styles analysed, the one students preferred the most was the authority-oriented learning style. That suggest students preferred teacher to give them lost of examples, show them how to do thing or demonstrate ways of thinking, and apply language concepts in different situations directly.